Vaccinia Virions Deficient in Transcription Enzymes Lack a Nucleocapsid - McFadden, Baron D.H. (2012)
The poxvirus virion contains an inner tubular nucleocapsid structure. The nucleocapsid is apparently labile to conventional electron microscopy fixation procedures and has therefore been largely ignored for decades. Advancements in electron microscopy sample preparation, notably high pressure freezing, better preserve the nucleocapsid structure. Using high pressure freezing and electron microscopy, we have compared the virion structures of wt virus and mutant viruses known to be deficient in packaging of viral transcription enzymes. We show that the mutant viruses lack a defined nucleocapsid. These results support the hypothesis that the nucleocapsid contains the viral DNA genome complexed with viral transcription enzymes and structural proteins. The studies open the door to further investigation of the composition and ultrastructure of the poxvirus nucleocapsid.